PROSES PENYUSUNAN PERUNDANG-UNDANGAN DITINJAU DARI HUKUM DAN KEBIJAKAN PUBLIK - Nina Yolanda (The Juris, 2022)
Not a few laws and regulations that have been passed by the Indonesian government are tested in the Constitutional Court. This phenomenon shows how important it is for lawmakers and public policy makers to always link law-making with the public policy process, especially at the formulation stage so that the law made has an established substance and strengthens public policy at the implementation stage. This study aims to find and explain the relationship between law and public policy and the stages of the policy formulation process for drafting a bill. This type of research uses a descriptive qualitative approach using a documentation study. Based on the results of the study, the authors conclude that the relationship between law and public policy in the field of study of public policy formulation lies in the similarity of processes, mutual support and mutual strengthening.